2020
DOI: 10.1163/15685411-bja10003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characterisation and molecular phylogeny of several species of Criconematina (Nematoda: Tylenchida) associated with turfgrass in Korea, as inferred from ribosomal and mitochondrial DNA

Abstract: SummarySix species belonging to the Criconematina, including a morphologically cryptic population within the Mesocriconema curvatum-group, are characterised based on integrative taxonomy based on morphological and molecular phylogenetic inferences from analyses of the 28S-rRNA, ITS-rRNA and COI gene sequences. Mesocriconema sp. 1 is morphologically similar to M. nebraskense and M. curvatum, differing from M. curvatum by the occasional presence of 1-2 anastomoses and a relatively higher R value, and from M. neb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…Phylogenetic relationships of P. nanus within selected Paratylenchus are given in Figure 4 Sequence of P. nanus from Virginia was identical to that of P. nanus type A from California. New sequence of P. projectus from North Dakota was identical to those of previously identified as P. nanus type B from South Africa (Van den Berg et al, 2014) or as P. nanus from North Dakota (Upadhaya et al, 2019a, b) and South Korea (Mwamula et al, 2020), and now all considered as P. projectus. Figure 5: Phylogenetic relationships of Paratylenchus nanus with other related species: Bayesian 50% majority rule consensus tree from two runs as inferred from analysis of the COI gene sequence alignment under the GTR + I + G model.…”
Section: The Its Of Rrna Genesupporting
confidence: 76%
“…Phylogenetic relationships of P. nanus within selected Paratylenchus are given in Figure 4 Sequence of P. nanus from Virginia was identical to that of P. nanus type A from California. New sequence of P. projectus from North Dakota was identical to those of previously identified as P. nanus type B from South Africa (Van den Berg et al, 2014) or as P. nanus from North Dakota (Upadhaya et al, 2019a, b) and South Korea (Mwamula et al, 2020), and now all considered as P. projectus. Figure 5: Phylogenetic relationships of Paratylenchus nanus with other related species: Bayesian 50% majority rule consensus tree from two runs as inferred from analysis of the COI gene sequence alignment under the GTR + I + G model.…”
Section: The Its Of Rrna Genesupporting
confidence: 76%
“…Van den Berg et al [ 22 ] reported two sibling species of P. nanus with different genotypes—type A and type B (the latter of which was recently transferred to P. projectus ) [ 61 ]. This correction suggests that the available 28S (MN720102–MN720103) and COI (MN734387 and MN734388) sequences of P. nanus from South Korea [ 48 ] were misidentified as they were found to be identical to the P. projectus sequences. Paratylenchus nanus is very similar to P. projectus and P. neoamblycephalus .…”
Section: Resultsmentioning
confidence: 99%
“…The new sequences for each gene (D2-D3 of 28S, ITS, 18S rRNA and COI ) were aligned using Clustal X 1.83 [ 104 ] with their corresponding published gene sequences [ 22 , 24 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Outgroup taxa for each dataset were chosen based on previously published data [ 105 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mesocriconema curvatum has a broad geographic distribution (Wouts 2006), covering almost all continents with reports of its occurrence from the United States (Zeng et al 2012), Europe (Castillo and Gómez-Barcina 1993;Winiszewska et al 2012Winiszewska et al , 2017, Asia (Choi and Geraert 1975;Mwamula et al 2020) and Africa (Lamberti et al 1991;De Waele et al 1998). In general this species has agricultural associations; however, it was also found in uncultivated grasslands (Powers et al 2014).…”
Section: Resultsmentioning
confidence: 99%